EMCDDA-Europol 2016: annual report on the implementation of Council Decision 2005/387/JHA : in accordance with Article 10 of Council Decision 2005/387/JHA on the information exchange, risk assessment and control of new psychoactive substances (Implementation reports, 2017)
This report presents the key activities performed by the EMCDDA and Europol in 2016, with details on all the relevant activities in support of the implementation of Council Decision 2005/387/JHA on the information exchange, risk assessment and control of new psychoactive substances, including new psychoactive substances notified in 2016, Joint Reports produced, risk assessments conducted and public health alerts and advisories issued.